Hypercysteinemia, A Potential Risk Factor for Central Obesity and Related Disorders in Azores, Portugal. (20th June 2019) - Lima, Ana; Ferin, Rita; Bourbon, Mafalda; Baptista, José; Pavão, M. Leonor
Abstract : In Azores, the standardized mortality rate for coronary artery disease (CAD) is nearly the double when compared to mainland Portugal. The aim of this study was to compare the prevalence of conventional CAD risk factors, as well as the plasma aminothiol profile (and its major determinants), between two groups of healthy subjects from Ponta Delgada (in Azores) and Lisbon (in mainland) cities, searching for precocious biomarker(s) of the disease. The study groups consisted of 101 healthy volunteers from Ponta Delgada (PDL) and 121 from Lisbon, aged 20–69 years. No differences in the prevalence of classical CAD risk factors were found between the study groups, except in physical inactivity and related central obesity, which were both higher in PDL men than in those from Lisbon. Hypercysteinemia, which seems to result from sulfur-rich amino acid diets and/or vitamin B12 malabsorption, revealed to be significantly more prevalent in PDL vs. Lisbon subjects (18% vs. 4%, P = 0.001 ), namely, in male gender. Moreover, plasma Cys levels predicted waist circumference ( β coefficient = 0.102, P = 0.032 ) and concomitant central obesity and were also associated with insulin resistance. Nevertheless, hyperhomocysteinemia prevalence was similar in both groups, despite the fact that PDL subjects exhibited a higher rate of vitamin B12 deficiency compared to those from Lisbon (19% vs. 6%, P = 0.003 ). Owing to the nature of this study design, a cause-effect relationship between high plasma Cys levels and central obesity or CAD risk could not be derived, but results strongly suggest that hypercysteinemia is a potential risk factor for metabolic disorders, i.e., obesity and insulin resistance, and CAD in Azores, a hypothesis that asks for confirmation through further large prospective studies.